2003
DOI: 10.1128/jvi.77.11.6556-6561.2003
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Herpes Simplex Virus Type 1 Latency-Associated Transcript Sequences That both Inhibit Apoptosis and Enhance the Spontaneous Reactivation Phenotype

Abstract: The herpes simplex virus type 1 (HSV-1) latency-associated transcript (LAT) gene is essential for the high spontaneous and induced reactivation phenotype of HSV-1 in the rabbit ocular model and for the high induced reactivation phenotype in the mouse ocular model. Recently we showed that LAT has an antiapoptosis function, and we hypothesized that LAT's ability to inhibit apoptosis played an important role in LAT's ability to enhance the reactivation phenotype. Expression of just the first 1.5 kb of the 8.3-kb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
63
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 19 publications
0
63
0
Order By: Relevance
“…It is also possible that AKT promotes cell survival after serum withdrawal and additional signalling pathways promote neurite outgrowth. Several studies have demonstrated that LAT inhibits apoptosis (Hamza et al, 2007;Inman et al, 2001;Jin et al, , 2002Jin et al, , , 2003Jin et al, , , 2004Peng et al, 2003Peng et al, , 2004Perng et al, 2000), but this study was the first to link AKT to the anti-apoptosis functions encoded within LAT coding sequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that AKT promotes cell survival after serum withdrawal and additional signalling pathways promote neurite outgrowth. Several studies have demonstrated that LAT inhibits apoptosis (Hamza et al, 2007;Inman et al, 2001;Jin et al, , 2002Jin et al, , , 2003Jin et al, , , 2004Peng et al, 2003Peng et al, , 2004Perng et al, 2000), but this study was the first to link AKT to the anti-apoptosis functions encoded within LAT coding sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, LAT can inhibit caspase 8-or caspase 9-induced apoptosis (Henderson et al, 2002;Jin et al, 2003;Peng et al, 2004), the two major apoptotic pathways (Krueger et al, 2001;Schmitz et al, 2000;Wang, 2001). The anti-apoptosis functions of LAT correlate with promoting spontaneous reactivation (Inman et al, 2001;Jin et al, 2003) and appear to be the crucial function of LAT because three different anti-apoptosis genes restore wt levels of spontaneous reactivation to a LAT null mutant virus (Jin et al, 2005(Jin et al, , 2008Mott et al, 2003;Perng et al, 2002b). LAT also represses productive viral gene expression in TG of mice during acute infection (Chen et al, 1997b;Garber et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…LAT plays an important role in the HSV latency-reactivation cycle since LAT null mutants have significantly reduced reactivation phenotypes in mice and rabbits while otherwise having wild-type like replication [5][6][7][8][9][10][11]. LAT has anti-apoptosis activity [12][13][14][15][16][17][18][19]. Mutants in which LAT is replaced by an alternative anti-apoptosis gene have efficient, wild-type like reactivation phenotypes [20][21][22], indicating that LAT's anti-apoptosis activity is sufficient to account for LAT's ability to support the wild-type reactivation phenotype in experimental animal models.…”
mentioning
confidence: 99%
“…Recent studies have demonstrated that HSV-1 LAT inhibits apoptosis of neurons, which is hypothesized to enhance the establishment of latency (2,13,36,45,76,77,81). However, HSV-2…”
Section: Mechanism Of Action Of Latmentioning
confidence: 99%